Enhancing Development Benefits to Local Communities in Hydropower Projects : Technical Workshop - World Bank (Washington, DC, 2013)
The technical workshop on enhancing development benefits to local communities in hydropower projects was held in Washington, D.C., on June 26, 2008. It was hosted by the Social Development Department (SDV) and Water Anchor (ETWWA) of the World Bank. The workshop aimed to provide a platform for a discussion of past and current practices, as well as how to construct development benefits mechanisms within the specific context of hydropower projects. It also provided a forum for sharing knowledge as to how development benefits mechanisms may be applied to Bank-financed projects. The workshop had five sessions and brought together more than 60 experts from different sectors in different regions of the World Bank. Sixteen speakers gave presentations. The workshop had discussions on enhancing development benefits to local communities in hydropower projects and also covered issues pertaining to the broader range of benefit-sharing, including World Bank engagement in hydropower projects, legacy of hydropower, notion evolution, approaches and mechanisms, and good practices in benefit-sharing of hydropower projects. A range of mechanisms are available to enhance and share benefits. Benefit-sharing consists of a combination of monetary and non-monetary mechanisms adapted to specific project contexts. Monetary development benefits are linked largely to economic rent, fair distribution, full compensation, entitlements, national priorities, and optimization of opportunities, and include basically taxation, royalties, preferential rates, revenue sharing, development funds, and joint ownership. The non-monetary development benefits include, for example, allocation of fishing rights in reservoirs; priority hiring of local community members during construction; start-up support for local companies; capacity building; multipurpose infrastructure; rural electrification; and access to improved infrastructure.